The liturgical sermons / Volume 3 The Durham and Lincoln collections, Sermons 47-84 / Aelred of Rievaulx ; translated by Kathryn Krug, Lewis White, and the Catena Scholarium ; introduction by Ann Astell - Aelred, von Rievaulx, Abt (The liturgical sermons, 2018)
Aelred, abbot of the Yorkshire Cistercian abbey of Rievaulx from 1147 to 1167, wrote six spiritual treatises, seven historical treatises, and 182 liturgical sermons, most of which he delivered as chapter talks to his monks. Translations of the first twenty-eight of these sermons appeared in CF 58 in 2001, translated by Theodore Berkeley and M. Basil Pennington, and sermons twenty-nine through forty-six appeared in CF 77 in 2015, translated by Marie Anne Mayeski. The current volume contains thirty-eight sermons for feasts from Advent through the Nativity of Mary, taken from the Durham and Lincoln collections, edited by Gaetano Raciti in CCCM 2B. (Publisher)